EVALUASI PROGRAM BEASISWA KOMUNITAS ADAT TERPENCIL DI DINAS PENDIDIKAN KABUPATEN BENGKALIS - Yeyen Suhana; Azhar Azhar; Rr. Sri Kartikowati (Universitas Riau, 2019)
The research aims to get definition of implementation scholarship programe of indigenous community in education department Bengkalis regency. Especially : (1) The scholarship programe of indigenous communities; (2) Focus of programe input the expediency human resource, facilities and infrastructure, fund and programe budget; (3) The process program include the time of implementation programe, the mechanism of implementation program, the factors inhibitors of implementation program and organization of partnership; (4) The product of programe include quality and quantity obtained from organizers scholarship program of indigenous communities and indigenous community’s student. The search method is evaluation search use of qualitative approachment and evaluation model used is CIPP ( Context, Input, Process, and Product). The technics data are documentation, interview, observation. The Source of data research are organizers, executor committe and comitte of verification of data, presentation of data, and conclusion. The data results are : (1) the context the program is said to be good because it is one of communities; (2) In input aspect is said to be good to expendiancy of human resource is the selection of members of the communities. While from the aspect of facilities and infrastructure have not complied with objective standart of indequate feasibility; (3) the program implemtation process is said to be less good because aspects only one that matches the feasibility standart. While from implmentation of time. Programe implementation mechanism is not suitable with guidelines so causing an inhibition of implementation; (4) the results of program implementation is said to be good, quantity and quality participants.